Computed Tomography–Measured Psoas Muscle Density as a Predictive Factor for Hypophosphatemia Associated With Refeeding. Issue 4 (20th July 2020) - Ireland, Megan; Lo, Wilson; Villarreal, Michael; Coleman, Lisa; Schubauer, Kathryn; Strassels, Scott; Peters, Zoe; Woodling, Karina; Evans, David; Wisler, Jon
Abstract: Background: Initiation of parenteral nutrition (PN) after a period of starvation can be complicated by refeeding syndrome (RFS). RFS is associated with electrolyte abnormalities including hypomagnesemia, hyponatremia, and hypophosphatemia. Risk factors include recent weight loss, low body mass index, and electrolyte deficiencies; however, these associations are not strong. We hypothesized that a validated measure of nutrition risk, computed tomography (CT)–measured psoas muscle density, can be used to predict the development of hypophosphatemia associated with RFS. Methods: A retrospective analysis of surgical patients initiated on PN with an abdominal CT scan within the past 3 months was conducted. CT‐measured psoas muscle density was assessed as a predictive variable for the development of electrolyte abnormalities. Daily electrolyte and clinical outcome measures were recorded. Results: One hundred nine patients were stratified based on Hounsfield unit average calculation (HUAC). The lowest 25th percentile of patients had HUAC <25. Low HUAC was associated with a significant percent decrease in phosphate levels from baseline to PN day 3 ( P < .01) and significant difference in serum phosphate value on PN day 3 ( P < .01). The low muscle density quartile also experienced longer days on the mechanical ventilator ( P = .01) compared with patients with a higher psoas muscle density. Conclusion: Psoas muscle density predicted the development of hypophosphatemia in patients initiated on PN. This measurement may aid in identifying patients at highest risk of experiencing RFS. A mean psoas HU <25 may prompt additional precautions, including additional phosphate replacement and slower initiation of PN.